Programmes, Projects and Learning Inquiries: Institutional Mediation of Innovation in Research for Development. (September 2014) - Ison, Ray; Carberry, Peter; Davies, Jocelyn; Hall, Andy; McMillan, Larelle; Maru, Yiheyis; Pengelly, Bruce; Reichelt, Nicole; Stirzaker, Richard; Wallis, Philip J.; Watson, Ian; Webb, Sara
This paper explores innovation processes and institutional change within research for development (R4D). It draws on learning by Australian participants associated with the implementation of a three-year Australian-funded food security R4D programme in Africa, and in particular a sub-component designed to support and elicit this learning. The authors critically examine this attempt at institutional innovation via the creation of a 'learning project' (LP) in a larger programme. For systemic innovation to be achieved, it is concluded that the system of concern must envisage institutional innovation and change within the donor and external research organizations as well as with project recipients and collaborative partners. Institutional constraints and opportunities are explored, including how the overall approach to learning in this programme could have been reframed as an organizational innovation platform (IP), designing, managing and evaluating IPs at different systemic levels of governance – including within the collaborative programme with African partners, in the constituent in-country projects, in the collaborating Australian organizations and at the level of personal practice.